2021
DOI: 10.1155/2021/5557309
|View full text |Cite|
|
Sign up to set email alerts
|

Urinary Angiogenin as a Marker for Bladder Cancer: A Meta-Analysis

Abstract: Aims. Bladder cancer (BCa) is a common cancer in North America and Europe that carries considerable morbidity and mortality. A reliable biomarker for early detection of the bladder is crucial for improving the prognosis of BCA. In this meta-analysis, we examine the diagnostic role of the angiogenin (ANG) protein in patients’ urine with bladder neoplasm. Methods. We performed a systematic literature search using ScienceDirect, Web of Science, PubMed/MEDLINE, Scopus, Google Scholar, and Embase, up to 10th Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…ANG is a multifunctional protein known to induce blood vessel formation and is a potential biomarker for cardiac deterioration [20] and several types of cancers [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANG is a multifunctional protein known to induce blood vessel formation and is a potential biomarker for cardiac deterioration [20] and several types of cancers [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…ANG is a multifunctional protein known to induce blood vessel formation and is a potential biomarker for cardiac deterioration [ 20 ] and several types of cancers [ 24 , 25 , 26 ]. Within this context, we studied the effects of improving vitamin D status in circulating ANG and whether it is associated with other known cardiometabolic indices in vitamin D-deficient adults.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ANG may be a good diagnostic marker for monitoring the progression of BC [ 39 ]. A previous study on the diagnostic role of urinary ANG in patients with bladder tumours has reported a sensitivity of 0.71 (95 % CI: 0.66–0.75), specificity of 0.78 (95 % CI: 0.73–0.81), LR+ of 3.34 (95 % CI: 2.02–5.53), LR-of 0.37 (95 % CI: 0.32–0.44), DOR of 9.99 (95 % CI: 4.69–21.28), and AUC of 0.789 and Q∗ index of 0.726, indicating the diagnostic value of urinary ANG in identifying BC [ 52 ].…”
Section: Application Value Of Ang In Cancermentioning
confidence: 99%
“…For this reason, a meta-analysis [ 58 ] of ANG as a potential marker of BCa was performed. It showed a pooled sensitivity of 0.71, specificity of 0.78, and AUC of 0.789 ( Table 7 ), which gives a chance to use ANG in diagnosing BCa.…”
Section: What Is New In the Last Two Years?mentioning
confidence: 99%